DISEASES ASSOCIATED WITH GLUCOSEMETABOLISM, THEIR ETIOLOGY, ANDPREVENTIVE MEASURES - Ahmadjonov Qudratillo Mashrabboy ogli; Ahmadjonova Oysha Mamasidiq qizi (Western European Studies, 2025)
This article discusses diseases associated with glucose metabolism: type 1 diabetes, type 2 diabetes, gestational diabetes, and hypoglycemia. Additionally, it presents several scientific findings about glucose being the main source of energy in the human body and how its metabolic disruption can lead to serious pathological conditions. The article includes information about type 1 diabetes, which involves the autoimmune destruction of insulinproducing beta cells, and type 2 diabetes, which is associated with the progression of insulin resistance
Keywords: Glucose; metabolism; type 1 diabetes